Kesadaran Politik Era Pandemi Studi Pemilihan Kepala Daerah Surabaya 2020 Di Kelurahan Medokan Ayu - Akmal, Firman (Indonesian Journal of Political Studies, 2023)
This research originated from the author's interest in seeing the 2020 Surabaya Regional Head Election which was held concurrently with the Covid-19 Pandemic. The formulation of the problem from this research is how is the political awareness of the people of the Medokan Ayu Village in the 2020 Surabaya Regional Head Election, what is the strategy carried out by the (KPU) Surabaya City Election Commission to increase public interest in voting during a pandemic, what efforts have been made by candidate pairs or political parties to invite the public to vote during a pandemic, and how the people of the Medokan Ayu Village interpret political awareness from the invitation of the KPU and candidate pairs or political parties in the 2020 Surabaya City elections. Researchers used a qualitative research method with a case study approach. In qualitative research, researchers used data collection techniques by interviewing and documentation as well as Paul Goren's theory of political values and political awareness. From the research findings, it was discovered that the political awareness of the community in Medokan Ayu Subdistrict, Surabaya City, is already good, but it is not yet optimal and does not meet the target set by the Surabaya City Election Commission (KPU). There are several factors that contribute to the increase in political awareness among the community in Medokan Ayu Subdistrict, including: political socialization conducted by the Surabaya City Election Commission, political socialization by political parties, and the campaign activities of the mayoral and vice-mayoral candidates. The Surabaya City Election Commission has implemented political socialization strategies through social media and electronic media, but it needs to be evaluated further to effectively reach all levels of society and make them understand the importance of political awareness. Both pairs of candidates and their supporting parties have conducted campaigns through social media, but it often feels like a formality. The content created does not seem to resonate with the Surabaya community. The candidates prefer direct interactions with the community, despite limitations on the number of people they can meet. Virtual campaigns using online media are not yet 100% optimal and need to be re-evaluated to maximize reaching new voters.